Sensors, Circuits & Instrumentation Systems : Extended Papers 2017 - Derbel, Faouzi; Derbel, Nabil; Kanoun, Olfa (Advances in Systems, Signals and Devices ;, 2018)
Signal Processing is one of the large specializations in electrical engineering, mechanical engineering and computer sciences. It derives input from physics, mathematics and is an indispensable feature of all natural- and life sciences in research and in application. The snew series "Advanced Issues on Signals, Systems and Devices" presents original publications mainly from speakers on the International Conferences on Signal Systems and Devices but also from other international authors. The Conference is a forum for researchers and specialists in different fields covering all types of sensors and measurement systems as for example: Biomedical and Environmental Measurements & Instrumentation; Optical, Chemical and Biomedical Sensors; Mechanical and Thermal Sensors; Micro-Sensors and MEMS-Technology; Nano Sensors, Nano Systems and Nano Technology; Spectroscopy Methods; Signal Processing and Modelling; Multi Sensor Data Fusion; Data Acquisition & Distributed Measurements; Medical and Environmental Applications; Circuit Test, Device Characterization and Modelling; Custom and Semi-Custom Circuits; Analog Circuit Design; Low-Voltage, Low-Power VLSI Design; Hardware Implementation; Materials, Devices and Interconnects; Packaging and Reliability; Battery Monitoring: Impedance Spectroscopy for Measurement and Sensor Solutions; Energy Harvesting and Wireless power Transfer Systems; Wireless Sensor Networks in Industrial Plants This first volume of the new series mainly devotes to the most recent research and implementation of sensors-, circuit systems in signal processing, energy harvesting, nano- and molecular electronics.